Industrial training briefing for Bachelor of applied science in data analytics with honors - Sahimel Azwal, Sulaiman (2023)
FEBRUARY 3, 2023, UMP PAYA BESAR - An industrial training briefing was held at Block Z, UMP Paya Besar.